Analisis Kesalahan Berbahasa Bidang Morfologi pada Baliho/Pamflet di Sekitar UIN Raden Mas Said Surakarta - Septiana, Nanda Fauzi; Ningrum, Rosa Widya (Kajian Bahasa dan Sastra (KABASTRA), 2023)
Language errors can occur in any condition, even when someone is learning a language. This language error can also occur due to ignorance of the community and lack of public knowledge. There are many language errors, one of which is at the morphological level. The purpose of this study is to describe various language errors found on billboards / pamphlets around UIN Raden Mas Said Surakarta. The choice of the place is because many students buy food and work part-time in shops or stalls around UIN Raden Mas Said. The research method in this study is descriptive qualitative, with research data in the form of billboards and pamphlets. From this study, 7 data were found, namely related to standard and non-standard word errors, hyphen writing, the use of spaces, and writing letters. From the analysis that has been done, the conclusion is that there are still many writing errors in pamphlets or billboards around UIN Raden Mas Said still. This happens because of the lack of awareness and attention from the author to write the correct Indonesian and follow PUEBI and EYD.